Understanding patient engagement in health system decision-making: a co-designed scoping review - McCarron, Tamara L. (Syst Rev, 2019)
BACKGROUND: With healthcare striving to shift to a more person-centered delivery model, patient and family involvement must have a bigger role in shaping this. While many initiatives involving patients and family members focus on self-care, a broader understanding of patient participation is necessary. Ensuring a viable and sustainable critical number of qualified patients and family members to support this shift will be of utmost importance. The purpose of this study was to understand how health systems are intentionally investing in the training and skill development of patients and family members. METHODS: Patient co-investigators and researchers conducted a scoping review of the existing literature on methods adopted by healthcare systems to build the skills and capacity of patients to participate in healthcare decision-making using a recognized methodological framework. Six electronic databases were searched to identify studies. Two independent reviewers screened titles and abstracts and full-text papers for inclusion. The research team independently extracted data. Any disagreements were resolved by achieving consensus through discussion. Quantitative and qualitative content synthesis, as well as a quality assessment, was conducted. RESULTS: After eliminating duplicates, the search resulted in 9428 abstracts. Four hundred fifty-eight articles were reviewed and 15 articles were included. Four themes emerged: forums (33%), patient instructors (20%), workshops (33%), and co-design (13%). Four of the identified studies measured the impact and overall effectiveness of the respective programs. Examples of how patient and family members were supported (invested in) included advocacy training to support future involvement in engagement activities, a training program to conduct patient-led research, involvement in an immersive experience-based co-design initiative, and involvement in training pharmacy students. Overall, these studies found positive outcomes when patients and family members were recipients of these opportunities. CONCLUSIONS: The results of this scoping review demonstrate that an evidence base around programs to advance patient engagement is largely absent. An opportunity exists for further research to identify strategies and measures to support patient engagement in healthcare decision-making. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13643-019-0994-8) contains supplementary material, which is available to authorized users.